Physical, Chemical Quality and Constituent of Amoniated Cassava Peel with Various Levels of Urea Addition - Farida Fathul; Erwanto Erwanto; Agung Kusuma Wijaya; Akhmad Dakhlan; Fitria Tsani Farda; Etha Azizah Hasiib (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
Cassava peel is a waste from the cassava plant which has the potential to be used as ruminant animal feed. Processing of cassava skin with ammonia needs to be done to improve the quality of cassava skin. The research was conducted to determine the physical and chemical quality of cassava peels after amoniation. The study was analyzed using a completely randomized design (CRD) and the significant results were further tested using Duncan's multiple range test (DMRT). The treatment was T1 (cassava peels + 0kg urea); T2 (cassava peels + 0.02kg urea) ; T3 (Cassava peels + 0.04kg urea). Each treatment consisted of 5 repetitions. The organoleptic test was carried out with 30 test participants. The physical tests observed were color, texture and aroma. Chemical quality was determined through proximate analysis and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). Variables in the chemical quality test included dry matter, ash, crude protein, ether extract and crude fiber of cassava peels. The results showed that ammoniation of cassava peels affected the physical and chemical qualities of cassava peels (P<0.05). Ammoniation of cassava peel increases protein content up to 23.01% (T3) and reduces crude fiber up to 7.92% (T2). Increasing the level of urea can increase the process of degradation of starch structure in cassava peels.